Ireland : Selected Issues. (IMF Staff Country Reports; Country Report, 2019)
This Selected Issues paper examines the past and present impact of personal income tax reform in Ireland. Personal income in Ireland is taxed under two distinct schemes. Changes in Ireland's personal income taxation have been procyclical and created vulnerabilities to public finances. The reduction in personal income taxes during the boom has been broad based, albeit more for low-income taxpayers. With somewhat shrinking corporate profits during the crisis, personal income taxation was increased. The reformed income tax would reduce the vulnerability of public finances to interplay of corporate (CIT) revenues and reduce procyclicality. A robust, stable income tax system performs a stabilizing role over the business cycle, while the additional CIT revenues during booms could be saved as buffers to be used for smoothing downturns or to reduce the still high public debt. Post-2014, income taxes have been reduced again, fueling the recovery in domestic demand. The Income Tax could be further amended to enhance incentives to work, while safeguarding the progressivity of the system.